Responding to policy makers’ evaluation needs: combining experimental and quasi-experimental approaches to estimate the impact of performance based financing in Burkina Faso - De Allegri, Manuela; Lohmann, Julia; Souares-Coutant, Aurélia; Hillebrecht, Michael; Hamadou, Saidou; Hien, Hervé; Haidara, Ousmane; Robyn, Paul Jacob (BMC health services research, 2019)
The last two decades have seen a growing recognition of the need to expand the impact evaluation toolbox from an exclusive focus on randomized controlled trials to including quasi-experimental approaches. This appears to be particularly relevant when evaluation complex health interventions embedded in real-life settings often characterized by multiple research interests, limited researcher control, concurrently implemented policies and interventions, and other internal validity-threatening circumstances. To date, however, most studies described in the literature have employed either an exclusive experimental or an exclusive quasi-experimental approach.